REHABILITATION OF MILITARISTS INVOLVED IN COMBAT OPERATION AS A METHOD OF CRIME PREVENTION - Bakhmach, Andrii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Research objective: to determine the possibility of categorizing the rehabilitation of military personnel who have participated in combat operations as a standalone method within the system of crime prevention methods. Research methods: comparative analysis, systemic analysis, cognitive-analytical, and others. Results: the author concludes that the rehabilitation of military personnel who have participated in combat operations holds a significant place among other crime prevention methods concerning this category of individuals and can be considered as a separate crime prevention method requiring further research in this field. Discussion: the necessity of timely diagnosis of the psychophysical and emotional state of military personnel who have participated in combat operations and their subsequent rehabilitation based on the results of such diagnosis, the relevance of regulating the issue of mandatory diagnosis of the psychophysical and emotional state of military personnel and their rehabilitation after demobilization in regulatory and legal acts. Methods of crime prevention are typically divided by criminologists into general (or societal), special, and individual categories. General (societal) crime prevention involves the application of a system of measures that affect society as a whole and are aimed at neutralizing societal factors that serve as causes and conditions for criminal activity among the population. Such factors include poverty, unemployment, low levels of cultural development, poor quality of education, alcohol and drug abuse, homelessness, illegal migration, interethnic and other conflicts. Special measures for crime prevention are applied to specific social groups, individuals engaged in specific fields of activity, and certain groups of people, such as those classified by age, for whom there are grounds to believe they have an increased propensity for criminal behavior. We believe that measures aimed at preventing criminal offenses among military personnel who have participated in combat operations should be included in this category, considering them as a distinct social group.